Automation of Two Ubuntu Servers with Ansible and Telegram as Notifications - Wibowo, Gading Haryono; Widiasari, Indrastanti Ratna (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The purpose of this study was to determine the application of the server configuration automation system using Ansible tools on Ubuntu Server. This study describes a descriptive qualitative research that examines a problem based on what is observed through certain media. The stages of research carried out in designing Automation of Two Ubuntu Servers with Ansible and Telegram as Notifications. The results of this study display two execution results, namely the status of Success and Ended. Ended state is caused by unreacable or unconnected host. The suggestion for the further development of this research is that the application of the automation system can also be carried out on the Windows Server operating system, not only on the Ubuntu Server.